MEDIATISASI #STOPFOODWASTE: STUDI KASUS PADA GARDA PANGAN - Gabriela Laras Dewi Swastika (Jurnal Ilmu Komunikasi AKRAB, 2018)
On the support of embodiment of livable Surabaya, the endeavors do not merely come from the government control. Inhabitants of Surabaya are present to encourage improvement and sovereignty of their city. In this case, there is one independent organization who constantly and actively empower volunteerism and social action of #stopfoodwaste, named Garda Pangan. Garda Pangan has a mission to stop food waste and to process leftovers to be worth-eating food, yet to help others in need. There are two main problems in this research, firstly I want to examine how does mediatization come through Garda Pangan programs related to #stopfoodwaste and secondly how does mediatization bring the participatory culture through digital praxis. I put a case study using theory of mediatization to scrutiny that Garda Pangan addresses intersection of issues. The result of this research is that digital praxis which intertwined with offline practices can bring discourse co-creating. It also delivers a stronger participatory culture, not only limited by main producer, but also supported the co-players (co-creators). The main issue itself can be heard by wider public.